A comprehensive overview of common conducting polymer-based nanocomposites; Recent advances in design and applications. (5th November 2021) - Raza, Saleem; Li, Xuelian; Soyekwo, Faizal; Liao, Dan; Xiang, Yijing; Liu, Changkun
Graphical abstract: Highlights: In the present review article, we focus on the synthetic routs and important applications of conducting polymers. Their recently advanced conducting materials and their important developments. Outline the important properties of some selected conducting monomers. Highlights the new research directions on the bases of current trends. Abstract: Currently, conducting polymers have attracted tremendous attention due to their unique characteristics and significant applications, such as ionic conductivity, electroanalytical technique, optical transparency, metal-like conductivity, environmental pollutant-sensitive materials, and mechanical flexibility. There is an urgent need to develop momentum in the utilization of conducting polymers for the preparation of special types of conducting nanocomposites from both commercial and other essential perspectives. Traditional material preparation procedures suffer from various shortcomings such as blank determination, sample preparation, calibration, need for skilled operators, time-consuming techniques, non-universal approaches, and high cost. The objective of this review article is to provide details regarding the fabrication of conducting polymer-based nanocomposites for continuous and different advanced materials monitoring and other important applications. Particularly, attention has been paid towards the design, classification, and the development of nanocomposites of conducting polymers (CP) and their applications for the elimination of environmental pollutants present in the ecosystem. We primarily emphasize the significant applications and synthesis routes of conducting polymers and the nanocomposites from the perspectives of biomedical, energy, photocatalysis, environmental, and sensor applications, because they all are closely related areas and have been widely explored. Moreover, we discuss some important fundamental research trends in fabrication, raw material sources, and newly developed approaches and highlight new research directions.